2022
DOI: 10.3389/ffgc.2022.738568
|View full text |Cite
|
Sign up to set email alerts
|

Soil Bacterial Community Along an Altitudinal Gradient in the Sumaco, a Stratovolcano in the Amazon Region

Abstract: Our study is a pioneering exploration of the microbiome in the soil of the Sumaco stratovolcano and an assessment of the effects of an elevational gradient and related physicochemical soil parameters on richness and community structure. The Sumaco, as an isolated Amazonian stratovolcano, may be among one of the least studied ecosystems in Ecuador and perhaps the Amazon region. Universal patterns remain unresolved or available information inconclusive to establish a supported consensus on general governing proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 78 publications
(79 reference statements)
0
2
0
Order By: Relevance
“…Correlations between elevation and diversity in microbial ecology can mask several underlying ecological and physicochemical parameters (Lanzén et al, 2016). Previous studies have found environmental parameters that were significantly independent of elevation, and where the latter factor was secondary to other parameters in explaining the structure of bacterial communities (Fierer et al, 2011;Díaz et al, 2022). Although we acknowledge the possibility of confounding or unaccounted factors that could be underlying elevation as a significant component for bacterial diversity, such as soil moisture, soil nutrient status, substrate availability, and substrate quality, (Meier et al, 2010;Nottingham et al, 2015), we have also included as part of our assessment a set of 18 physicochemical parameters, whose correlations with the observed community diversity and structure are discussed in the next paragraphs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Correlations between elevation and diversity in microbial ecology can mask several underlying ecological and physicochemical parameters (Lanzén et al, 2016). Previous studies have found environmental parameters that were significantly independent of elevation, and where the latter factor was secondary to other parameters in explaining the structure of bacterial communities (Fierer et al, 2011;Díaz et al, 2022). Although we acknowledge the possibility of confounding or unaccounted factors that could be underlying elevation as a significant component for bacterial diversity, such as soil moisture, soil nutrient status, substrate availability, and substrate quality, (Meier et al, 2010;Nottingham et al, 2015), we have also included as part of our assessment a set of 18 physicochemical parameters, whose correlations with the observed community diversity and structure are discussed in the next paragraphs.…”
Section: Discussionmentioning
confidence: 99%
“…Increments in biodiversity at lower glacial altitudes have been reported not only at the prokaryotic scale but also for macroinvertebrates and other groups of multicellular organisms (Milner et al, 2001;Jacobsen and Dangles, 2012;Cauvy-Fraunié and Dangles, 2019). A recent synthesis on the effect of altitude on soil bacteria diversity can be found in Díaz et al (2022), which shows that the issue is currently not fully understood and lacks universal consensus.…”
Section: Discussionmentioning
confidence: 99%